Antibacterial spectrum of four compounds from yeasts in koumiss - Chen, Y.J.; Du, C.G.; Guo, Y.Q.; Zhao, Y.F.; Aorigele, C.; Wang, C.J.; Simujide, H.; Aqima, W.; Zhang, X.Y. (Polish Journal of Veterinary Sciences, 2021)
Koumiss has beneficial therapeutic effects on bacterial diseases. Four antibacterial com- pounds from yeasts ( Kluyveromyces marxianus and Saccharomyces cerevisiae) in koumiss were evaluated for their antibacterial effects against three Gram-negative bacteria, three Gram-positive bacteria and five pathogenic Escherichia coli strains. The antibacterial compounds from yeasts in koumiss were extracted, and their main components were determined. The inhibition zones were analyzed, and their minimum inhibition concentrations (MICs) and minimum bactericidal concentrations (MBCs) were determined. Aqueous phases of Kluyveromyces marxianus and Saccharomyces cerevisiae at pH 2.0 and 8.0 produced larger inhibition zones than those in other phases, and then antibacterial compounds from K. marxianus (K2, pH=2.0; K8, pH=8.0) and S. cerevisiae (S2, pH=2.0; S8, pH=8.0) were obtained. Their main components were organic acids and killer toxins. K2 had more propanoic acid and S2 had more oxalic acid than others. The inhibition zones of K2, K8, S2 and S8 against three Gram-negative bacteria and three Gram-positive bacteria were 12.03-23.30 mm, their MICs were 0.01-0.13 g/mL, and MBCs were 0.03-0.50 g/mL. Meantime, the inhibition zones of K2, K8, S2 and S8 against five pathogenic E. coli were 16.10-25.26 mm, their MICs were 0.03-0.13 g/mL, and MBCs were 0.13-1.00 g/mL. These four antibacterial compounds from yeasts in koumiss had broad antibacterial spectrum. In addition, K2 and S2 were better than K8 and S8.
Keywords: Kluyveromyces marxianus; Saccharomyces cerevisiae; Escherichia coli; minimum inhibition concentration; minimum bactericidal concentration